2014
DOI: 10.1371/journal.pone.0086209
|View full text |Cite
|
Sign up to set email alerts
|

How Does Pollen Chemistry Impact Development and Feeding Behaviour of Polylectic Bees?

Abstract: Larvae and imagos of bees rely exclusively on floral rewards as a food source but host-plant range can vary greatly among bee species. While oligolectic species forage on pollen from a single family of host plants, polylectic bees, such as bumblebees, collect pollen from many families of plants. These polylectic species contend with interspecific variability in essential nutrients of their host-plants but we have only a limited understanding of the way in which chemicals and chemical combinations influence bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
190
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(199 citation statements)
references
References 61 publications
9
190
0
Order By: Relevance
“…The latter are consistent with previous studies suggesting that amino acid composition is conserved among plant species Weiner et al 2010). High total amino acid content and related nitrogen content have been reported to differ widely among plant species and to be positively correlated with larva weight and development, particularly with more than 20 % total protein content (Génissel et al 2002;Tasei and Aupinel 2008;Vanderplanck et al 2014b). Therefore, the pollen of Comarum palustre and Trifolium pratense might be considered to be of high chemical value, as they showed total amino acid content higher than 20 %, whereas the pollen of Cirsium palustre would be low-quality pollen.…”
Section: Quality Of Pollen Rewardssupporting
confidence: 92%
See 1 more Smart Citation
“…The latter are consistent with previous studies suggesting that amino acid composition is conserved among plant species Weiner et al 2010). High total amino acid content and related nitrogen content have been reported to differ widely among plant species and to be positively correlated with larva weight and development, particularly with more than 20 % total protein content (Génissel et al 2002;Tasei and Aupinel 2008;Vanderplanck et al 2014b). Therefore, the pollen of Comarum palustre and Trifolium pratense might be considered to be of high chemical value, as they showed total amino acid content higher than 20 %, whereas the pollen of Cirsium palustre would be low-quality pollen.…”
Section: Quality Of Pollen Rewardssupporting
confidence: 92%
“…Studies usually focus on the bumble bee's host plant use and foraging constancy (Carvell et al 2006;Connop et al 2010;Kleijn and Raemakers 2008), or on the pollen nutritive value of several plant species (Hagbery and Nieh 2012;Leonhardt and Blüthgen 2012;Tasei and Aupinel 2008;Vanderplanck et al 2014b). However, the bee's host plant choices coupled with the nectar and pollen quality of host plants have been rarely addressed (Hanley et al 2008;Leonhardt and Blüthgen 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They found that among 10 tested parameters, the most sensitive features to the different pollens were the mean weight of the larvae and the rate of discarded larvae. Similarly, Vanderplanck et al (2014b) found that B. terrestris colonies fed on Sorbus aucuparia and Cytisus scoparius pollen, produced larger larvae and fed less on nectar, compared to the other diets (Salix caprea, Calluna vulgaris, and Cistus sp. diets).…”
Section: Introductionmentioning
confidence: 80%
“…However, pollen nutritional quality varies widely among plant species, ranging from 2-60% protein and 1-20% lipids by weight (10,18); thus, it likely is critical that bees selectively collect pollen species with the necessary nutritional quality to support their needs (1). The protein and amino acid concentrations of pollen modulate immunocompetence in honey bees (16,19) and reproduction (ovary activation and larval development) in bumble bees (12,14,(20)(21)(22). Furthermore, lipids are key to a variety of physiological processes in insects, including molting hormone production (23), and high sterol content in pollen may increase bumble bee larval size and growth (21).…”
mentioning
confidence: 99%
“…The protein and amino acid concentrations of pollen modulate immunocompetence in honey bees (16,19) and reproduction (ovary activation and larval development) in bumble bees (12,14,(20)(21)(22). Furthermore, lipids are key to a variety of physiological processes in insects, including molting hormone production (23), and high sterol content in pollen may increase bumble bee larval size and growth (21). Recently, deficiency in linolenic fatty acid (an essential fatty acid) in honey bees has been linked to reduced learning and development of broodfood-producing glands (24).…”
mentioning
confidence: 99%